The Influence of Job Characteristics, Supervision, Employee Behavior and Work Discipline on the Work Effectiveness of Employees of the Housing and Settlement Area Office of Muara Enim Regency - Dedi Faureza Kartubi; Subahri Madjir; Darmin Darmin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The author conducted research with the aim of knowing and analyzing the influence of job characteristics, supervision, employee behavior and work discipline individually and collectively on the work effectiveness of employees of the Muara Enim Regency Housing and Settlement Area Office. The research method used in this study is a quantitative method using questionnaires distributed to respondents. Test the quality of the data by using the validity test, reliability test, normality test. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial test simultaneous test and the coefficient of determination. The results of the study explain that job characteristics have a significant effect on the work effectiveness of employees of the Housing and Settlement Area Office of Muara Enim Regency. Supervision has a significant effect on work effectiveness. Employee behavior has a significant effect on work effectiveness. Work discipline has a significant effect on work effectiveness. Job characteristics, supervision, employee behavior and work discipline have a significant joint effect on the effectiveness of the work of the employees of the Muara Enim District Housing and Settlement Area Office.